Efektivitas Program Kampus Mengajar dalam Meningkatkan Kemampuan Literasi dan Numerasi Siswa di Sekolah Dasar Inklusi - Indriani, Rusda; Safitri, Deta; Rahmayani, Nora; Fitri, Maulida; Muslim, Azis; Maulida, Dina; Fitria, Mia; Hidayat, Farid (Nusantara Journal of Education and Social Science, 2026)
This study aims to analyze the effectiveness of the Kampus Mengajar Program in improving the literacy and numeracy skills of students in an inclusive elementary school. The research subjects were fifth-grade students at SD Negeri Inklusi Banjang 2 (n = 11) who participated in learning assistance activities conducted by Kampus Mengajar student volunteers. The study employed a quantitative approach using a one-group pretest–posttest design. Data were collected through literacy and numeracy tests administered before and after the intervention. The normality test indicated that the data were normally distributed; therefore, comparative analysis was conducted using a paired sample t-test. The results revealed significant differences between pretest and posttest scores in both literacy (p < 0.001) and numeracy (p = 0.008). These findings indicate that the Kampus Mengajar Program is effective in enhancing students’ literacy and numeracy skills in the inclusive classroom setting.